2014
DOI: 10.1103/physreve.90.033314
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of discrete-particle models of spherical colloids: A multiparticle collision dynamics simulation study

Abstract: We investigate the hydrodynamic properties of a spherical colloid model, which is composed of a shell of point particles by hybrid mesoscale simulations, which combine molecular dynamics simulations for the sphere with the multiparticle collision dynamics approach for the fluid. Results are presented for the center-of-mass and angular velocity correlation functions. The simulation results are compared with theoretical results for a rigid colloid obtained as a solution of the Stokes equation with no-slip bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 75 publications
5
68
0
Order By: Relevance
“…In particular, the hydrodynamic correlations of the MPC fluid have been determined and it has been shown that they agree with the solutions of the fluctuating Landau-Lifshitz NavierStokes equations [25]. Moreover, the hydrodynamic correlations of embedded colloids [26][27][28][29][30][31] and polymers [32] have been calculated. Even more, MPC simulations have been successfully applied to verify the fluctuation relation for entropy production in shear flows [11].…”
Section: Introductionmentioning
confidence: 81%
“…In particular, the hydrodynamic correlations of the MPC fluid have been determined and it has been shown that they agree with the solutions of the fluctuating Landau-Lifshitz NavierStokes equations [25]. Moreover, the hydrodynamic correlations of embedded colloids [26][27][28][29][30][31] and polymers [32] have been calculated. Even more, MPC simulations have been successfully applied to verify the fluctuation relation for entropy production in shear flows [11].…”
Section: Introductionmentioning
confidence: 81%
“…A protein is represented by a spherical shell composed of point particles, which are connected by suitable elastic bonds to maintain its shape ( 35 ). The colloids are embedded in the MPC fluid to account for hydrodynamic interactions.…”
Section: Methodsmentioning
confidence: 99%
“…The colloids are embedded in the MPC fluid to account for hydrodynamic interactions. Calculations of colloid velocity correlation functions provide the correct hydrodynamic behavior on relevant length and time scales ( 35 ). Interactions between spherically symmetric colloids are described by the short-range attractive potential of Eq.…”
Section: Methodsmentioning
confidence: 99%
“…However, angular-m om entumconserving extensions have been introduced for both the stochastic rotation version of M PC (M P C -S R D + a) and the ' m.theers@fz-juelich.de T.winkler@fz-juelich.de PACS number(s): 47.11 ,-j , 02.70.Ns, 6 6 .20.-d A ndersen variant (M PC -A T + a) [17,18]. The M PC m ethod has successfully been applied to a broad range o f soft m atter system s ranging from equilibrium colloid [6,8,9,[19][20][21][22][23][24][25][26][27] and polym er [8,9,[28][29][30] solutions and, m ore importantly, nonequilibrium system s such as colloids [16,[31][32][33][34][35], poly mers [29,[36][37][38][39][40][41][42][43][44][45], vesicles [46], and cells [47,48] in flow fields, colloids in viscoelastic fluids [49][50][51], to selfpropelled spheres [52][53][54], rods …”
Section: Introductionmentioning
confidence: 99%